GENE EXPRESSION AND SEQUENCING TECHNIQUES OF TRANSCRIPTOME TO ELUCIDATE NOVEL FUNCTION FOR PHOSPHOLIPASE (S) ENZYME - PA Vora, M G Tyagi, S Saha, D Mukherjee, A Ramaswamy, (Journal of Biomedical and Pharmaceutical Research, 2018)
Sequencing of RNA, or RNA-Seq, is now a common method to analyze gene expression and to uncover novel RNA species. Aspects of RNA biogenesis and metabolism can be evaluated with specialized methods for cDNA library preparation. In this study, the review examines current RNA-Seq methods for general analysis of gene expression and several specific applications, including isoform and gene fusion detection, targeted sequencing and single-cell analysis.Elucidating the transcriptome may help in better understanding of phospholipase function and novel application in diagnostics and clinical therapeutics. Therefore this review article focusses on the transcriptome analysis of the phospholipase enzymes i.e phospholipase A2, D and C isozymes and characterizing their functional roles in specialized disorders or for therapy. Key words: RNA, sequencing, transcriptome, phospholipase D, gene, expression